Raising the Spirit of Sekaha Gong Kebyar Desa Ulian Through the Creation of "Sekar Jepun" Gending - I Nengah Sama; Saptono Saptono; Hendra Santosa (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2023)
Thematic KKN is a form of education that provides a learning experience for students outside the campus/university, which directly together with the community, identifies the potential that exists in the Village and also provides a solution to the problems that exist in the Village so that in thematic KKN it can develop the Village and provide solutions to the problems faced by the Villaexplain that in this Thematic KKN program, the authors chose partners in Ulian Village, Kintamani District, Bangli Regency. I chose a partner in Ulian Village because art was still lagging in Ulian Village, especially in musical arts. Therefore, the author aims to raise the spirit of the sekaha Gong Kebyar in Ulian Village by conducting Karawitan art training and building community enthusiasm in Ulian Village to preserve art, especially Karawitan Art. The results of this Thematic Community Service Program have positively impacted the people of Ulian Village and as a first step to awaken the arts, especially musical arts in Ulian Village. In this activity, it can be useful for the people in Ulian Village to develop their arts through musical training, and it is also useful for writers to learn to socialize in the community, improving their ability to think in collaboration.